DHA Suppresses Primary Macrophage Inflammatory Responses via Notch 1/ Jagged 1 Signaling - Ali, Mehboob (Sci Rep, 2016)
Persistent macrophages were observed in the lungs of murine offspring exposed to maternal LPS and neonatal hyperoxia. Maternal docosahexaenoic acid (DHA) supplementation prevented the accumulation of macrophages and improved lung development. We hypothesized that these macrophages are responsible for pathologies observed in this model and the effects of DHA supplementation. Primary macrophages were isolated from adult mice fed standard chow, control diets, or DHA supplemented diets. Macrophages were exposed to hyperoxia (O(2)) for 24 h and LPS for 6 h or 24 h. Our data demonstrate significant attenuation of Notch 1 and Jagged 1 protein levels in response to DHA supplementation in vivo but similar results were not evident in macrophages isolated from mice fed standard chow and supplemented with DHA in vitro. Co-culture of activated macrophages with MLE12 epithelial cells resulted in the release of high mobility group box 1 and leukotriene B(4) from the epithelial cells and this release was attenuated by DHA supplementation. Collectively, our data indicate that long term supplementation with DHA as observed in vivo, resulted in deceased Notch 1/Jagged 1 protein expression however, DHA supplementation in vitro was sufficient to suppress release LTB(4) and to protect epithelial cells in co-culture.